60 GHz BiCMOS active bandpass filters. (August 2019) - Chaturvedi, Saurabh; Božanić, Mladen; Sinha, Saurabh
Abstract: In this article, two 60 GHz active bandpass filters (BPFs) using the GlobalFoundries 0.13 μ m SiGe BiCMOS8HP process design kit are presented. To enhance the quality factor of a transmission line resonator, the complementary cross-coupled pair-based loss compensation method is used in the BPF design. The circuit simulation is performed with the Keysight Technologies Advanced Design System. The first active BPF with center frequency f c of 60.65 GHz shows a minimum insertion loss (IL) of 0.04 dB and best return loss (RL) of 25.13 dB in the passband. The second simulated active BPF with f c of 62.7 GHz exhibits a minimum IL of 0.01 dB and best RL of 27.82 dB in the passband.